Adaptive Arbitration Framework for Cross-Border ESG Dispute Resolution - Zaini Munawir S; Taufik Siregar (JURNAL AKTA, 2026)
The resolution of cross-border disputes involving Environmental, Social, and This study examines the effectiveness of arbitration as an adaptive mechanism for resolving cross-border disputes involving Environmental, Social, and Governance (ESG) issues. The increasing integration of sustainability standards, human rights principles, and corporate governance obligations into international trade and investment relationships has generated complex disputes that require flexible yet legally certain resolution mechanisms. This research aims to analyze how arbitration accommodates ESG-related conflicts and to assess the contribution of technological innovation in strengthening procedural efficiency and transparency. The study employed a qualitative normative approach using descriptive-analytical methods based on secondary data, including arbitral awards, bilateral and multilateral treaty frameworks, institutional reports, and recent scholarly literature. The findings demonstrate that arbitration provides procedural flexibility, neutrality, enforceability, and expert-based adjudication capable of addressing technical ESG dimensions. Furthermore, the incorporation of digital technologies such as Online Dispute Resolution (ODR), blockchain-based evidence management, and Artificial Intelligence (AI)-assisted document analysis enhances efficiency, transparency, and cross-border accessibility. However, challenges remain regarding enforcement inconsistencies, public policy limitations, and harmonization gaps among national legal systems. This research contributes by proposing an adaptive arbitration framework that integrates ethical standards, technological innovation, and ESG-sensitive interpretative approaches to ensure sustainability-oriented dispute resolution in the global legal order.